The adjuvant BcfA activates antigen presenting cells through TLR4 and supports TFH and TH1 while attenuating TH2 gene programming - Shamseldin, Mohamed M.; Read, Kaitlin A.; Hall, Jesse M.; Tuazon, Jasmine A.; Brown, Jessica M.; Guo, Myra; Gupta, Yash A.; Deora, Rajendar; Oestreich, Kenneth J.; Dubey, Purnima (Frontiers in Immunology, 2024)
Adjuvants added to subunit vaccines augment antigen-specific immune responses. One mechanism of adjuvant action is activation of pattern recognition receptors (PRRs) on innate immune cells. Bordetella colonization factor A (BcfA); an outer membrane protein with adjuvant function, activates TH1/TH17-polarized immune responses to protein antigens from Bordetella pertussis and SARS CoV-2. Unlike other adjuvants, BcfA does not elicit a TH2 response. To understand the mechanism of BcfA-driven TH1/TH17 vs. TH2 activation, we screened PRRs to identify pathways activated by BcfA and showed that BcfA activates antigen presenting cells through murine TLR4. We tested the role of this receptor in the BcfA-mediated activation of bone marrow-derived dendritic cells (BMDCs) using mice with germline deletion of TLR4. We found that BcfA-treated WT BMDCs upregulated expression of the costimulatory molecules CD40, CD80, and CD86 and produced IL-6, IL-12/23 p40, and TNF-α while TLR4 KO BMDCs were not activated. Furthermore, human PBMCs stimulated with BcfA produced IL-6. BcfA-stimulated murine BMDCs also exhibited increased uptake of the antigen DQ-OVA, supporting a role for BcfA in improving antigen presentation to T cells. BcfA further activated APCs in murine lungs.Using an in vitro TH cell polarization system, we found that BcfA-stimulated BMDC supernatant supported TFH and TH1 while suppressing TH2 gene programming. Overall, these data provide mechanistic understanding of how this novel adjuvant activates immune responses.